THE EFFECT OF EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE TOWARDS INTENTION IN ENTREPRENEURSHIP COLLEGE STUDENT - Radiman Radiman; Sukiman Sukiman; Rizal Agus (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze the effect of emotional intelligence on students 'entrepreneurial intentions, the effect of spiritual intelligence on students' entrepreneurial intentions and to analyze the effect of emotional intelligence and spiritual intelligence on student entrepreneurial intentions in the Management Study Program of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara . This study uses an explanatory research approach. The population in this study were all students of the Faculty of Economics and Business Management Study Program, Universitas Muhammadiyah Sumatera Utara . For those who become samples in this study amounted to 100 people. The types of data used are primary data and secondary data, the research data collection instruments used were questionnaires and interviews. The data analysis technique is multiple linear regression analysis. The results showed that partially, each variable of emotional intelligence and spiritual intelligence influenced students' entrepreneurial intentions. Simultaneously, the variables of emotional intelligence and spiritual intelligence affect the entrepreneurial intention of students in the Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara .Keywords: emotional intelligence, spiritual intelligence, entrepreneurial intentions